INVESTIGATION OF CONTAMINATION WITH ALPHA-CYPERMETHRIN MED IN AGRICULTURAL LANDS ON THE LEFT SIDE OF THE CITY OF MOSUL - Esraa ahmed saied; Mazin Nazar Fadhel; Nief Rahman (Scholar Express Journal, 2022)
Alpha-cypermethrin, an important pyrethroid insecticide, has been widely used for pest control in agriculture and parasite control in livestock farms. Major agricultural applications include the protection of oilseeds, pome fruits, peaches, fruit vegetables, berries, leafy vegetables, corn and tobacco. Alpha-cypermethrin has been marketed since late 1983. Concentrations of the pesticide vacypermethrin were determined because it is commonly used in agricultural lands on the left side of the city of Mosul. It is dangerous because of its high acute toxicity even at low concentrations. Therefore, its discovery in the environment is necessary in different environmental samples, including water (Tigris River, Wadi Danfali, Al-Khawser River) and soil samples from different areas of farms on the left side of the city of Mosul (Sherikhan, Rashidiya, Al-Muthanna, Al-Baath, Yaramjah) and plant samples from the same areas, which are (Lahana, cauliflower, beans). A new and highly sensitive spectrophotometric method has been developed for the determination of parts per million levels of the widely used cypermethrin insecticide. The method is based on the alkaline hydrolysis of cypermethrin to the cyanide ion, which also reacts with potassium iodide and the dye crystal violet. The maximum absorption of crystal violet dye formed at 595 nm was measured in acidic medium. Beer's law is subject to a concentration range of 5-20 mcg in a final solution volume of 25 mL. The molar absorbance and Sandell sensitivity were found to range between 0.147 (-0.642) ppm. The method is simple, sensitive and free from the interference of other pesticides and assorted ions. Finally, pyrethroid insecticides do not interfere with the proposed method, the method that was applied to determine cypermethrin in environmental samples was effective and satisfactory.
Keywords: Contamination; Alpha-Cypermethrin Med; Agricultural Lands